Distinct Mitochondria-Mediated T-Cell Apoptosis Responses in Children and Adults With Coronavirus Disease 2019. (10th August 2021) - Yang, Yang; Kuang, Liangjian; Li, Linhai; Wu, Yongjian; Zhong, Bei; Huang, Xi
Abstract: Background: Lymphopenia is a key feature for adult patients with coronavirus disease 2019 (COVID-19), although it is rarely observed in children. The underlying mechanism remains unclear. Methods: Immunohistochemical and flow cytometric analyses were used to compare the apoptotic rate of T cells from COVID-19 adults and children and apoptotic responses of adult and child T cells to COVID-19 pooled plasma. Biological properties of caspases and reactive oxygen species were assessed in T cells treated by COVID-19 pooled plasma. Results: Mitochondria apoptosis of peripheral T cells were identified in COVID-19 adult patient samples but not in the children. Furthermore, increased tumor necrosis factor-α and interleukin-6 in COVID-19 plasma induced mitochondria apoptosis and caused deoxyribonucleic acid damage by elevating reactive oxygen species levels of the adult T cells. However, the child T cells showed tolerance to mitochondrial apoptosis due to mitochondria autophagy. Activation of autophagy could decrease apoptotic sensitivity of the adult T cells to plasma from COVID-19 patients. Conclusions: Our results indicated that the mitochondrial apoptosis pathway was activated in T cells of COVID-19 adult patients specifically, which may shed light on the pathophysiological difference between adults and children infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 ). Abstract : IL-6 and TNF-α components in COVID-19 patient's plasma induced the mitochondria apoptosis of adult T cells. Activation of autophagy inhibited the apoptotic sensitivity of adult T cells to plasma from COVID-19 patients.